2015
DOI: 10.1016/j.jbi.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Text mining for pharmacovigilance: Using machine learning for drug name recognition and drug–drug interaction extraction and classification

Abstract: Pharmacovigilance (PV) is defined by the World Health Organization as the science and activities related to the detection, assessment, understanding and prevention of adverse effects or any other drug-related problem. An essential aspect in PV is to acquire knowledge about Drug-Drug Interactions (DDIs). The shared tasks on DDI-Extraction organized in 2011 and 2013 have pointed out the importance of this issue and provided benchmarks for: Drug Name Recognition, DDI extraction and DDI classification. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…For example, the WBI-NER system that ranked first in the SemEval-2013 Task 9.1 (Recognition and classification of pharmacological substances, DNR), [3] is based on a linearchain CRF with specialized features. Other similar systems for DNR [2,13] use various general-and domainspecific features. In CCE, the same approach (feature engineering + conventional ML classifier) has achieved the best results.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the WBI-NER system that ranked first in the SemEval-2013 Task 9.1 (Recognition and classification of pharmacological substances, DNR), [3] is based on a linearchain CRF with specialized features. Other similar systems for DNR [2,13] use various general-and domainspecific features. In CCE, the same approach (feature engineering + conventional ML classifier) has achieved the best results.…”
Section: Related Workmentioning
confidence: 99%
“…Current state-of-the-art ML methods follow a two-step process: 1) feature engineering and 2) automated classification. [1,2,3,4] The first step represents the text by numeric vectors using domainspecific knowledge. The second step refers to the task of classifying each word into a different named-entity class, with popular choices for the classifier being the linear-chain Conditional Random Fields (CRF), Structural Support Vector Machines (S-SVM) and maximumentropy classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…The framework of this active learning approach is a sequential process: initial model generation, querying, training, and iteration. The CRF Algorithm BIO approach was also studied by Ben Abacha et al [14]. The features for the CRF algorithm are formulated based on token and linguistics feature and semantic feature.…”
Section: Related Workmentioning
confidence: 99%
“…Our proposed method is evaluated on DrugBank and MedLine medical open dataset obtained from SemEval 2013 Competition task 9.1; see https://www.cs.york.ac.uk/semeval-2013/task9/, which is also used by [11, 12, 14]. The format of both medical texts is in English where some sentences contain drug name entities.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from close to 70% of DDI articles and >50% of ADRs articles being published in the last ten years. Automated approaches have been developed for the recognition and extraction of DDIs or ADRs alone 6–8 , and there is an increasing interest in identifying ADRs caused by DDIs using text-mining approaches 9 . Since DDIs may occur when two drugs interact with the same gene 8 or when one drug inhibits or induces the metabolic pathway of the other drug 10 , it has also been suggested that incorporating drug-gene interactions (DGIs) can enhance the prediction of DDIs 8 .…”
Section: Introductionmentioning
confidence: 99%